IMPROVING THE QUALITY OF EDUCATION AND ABSORPTION THROUGH THE ORGANIZATION OF COLLECTIVE ACTIVITIES IN THE COMPETITOR CLASSES (Web of Teachers: Inderscience Research, 2025)
This article analyzes ways to organize the importance and effectiveness of the role of team work in the Optional Case. Optional exercises will allow students to develop their talents and strengthen their knowledge, however, developing social skills through collective work. The team work will help read students to solve problems together, exchange ideas and achieving common purposes. The article will consider ways to increase the efficiency of collective work by methodological manuals, group works and training of students and creating Feeding Systems. It also emphasizes the importance of creating psychological support and a safe learning environment. The article offers practical recommendations aimed at developing collective work and serve to increase the efficiency of the educational process.